The Relationship Between Family Support with Self-Care for People with Diabetes Mellitus - Asnuddin, Asnuddin; Dioso, Regidor III (TRANSPUBLIKA INTERNATIONAL RESEARCH IN EXACT SCIENCES, 2025)
Diabetes mellitus (DM) is a chronic disease that requires long-term management, and family support plays an important role in helping patients perform self-care. This study aimed to determine the relationship between family support and self-care in people with diabetes mellitus. Using a quantitative approach with a cross-sectional design, the study involved a population of 147 diabetes mellitus patients, with 60 respondents selected through the Slovin Formula. Data were collected using questionnaires and analyzed with the Chi-Square test. The findings showed a significant relationship between family support and self-care in people with diabetes mellitus (P-value = 0.001). Patients who received high levels of family support were more disciplined in controlling their diet, engaging in physical activity, maintaining personal hygiene, and adhering to medication. These results indicate that family support significantly influences self-care abilities in people with diabetes mellitus, and thus, health workers should involve families in diabetes management programs to improve the effectiveness of patient care. Family members can help monitor the patient's health, provide emotional support, and reinforce positive health behaviors, ultimately contributing to better health outcomes for the patient. Given these findings, healthcare providers should consider incorporating family-centered care into diabetes management programs to improve patient compliance, reduce the burden of disease, and enhance the overall quality of care.